Construction work for electricity power lines (MENA Report, 2013)
Deposits and Guarantees required: The Contracting Authority requires that the supplier to meet their obligations arising from participation in procurement procedures provide a guarantee in accordance with [section] 67 of the Act. The amount of the security shall be fixed at the amount of 1,000,000 CZK.